MAGNETIC-PROPERTIES OF FE73.5CU1NB3(SIXB1-X)22.5 (X=0.4-0.8) ALLOY RIBBONS QUENCHED FROM DIFFERENT MELT TEMPERATURES - PI, WK; LIM, SH; NOH, TH; KIM, HJ; KANG, IK (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 1993)
The effects of the melt temperature on the magnetic properties of the nanocrystalline Fe73.5Cu1Nb3(Si0.6B0.4)22.5 alloy were previously investigated and it was found that the soft magnetic properties improve with increased melt temperature. In this paper, in order to examine the melt temperature effects of alloys with varying degree of glass forming ability, we investigate the magnetic properties of nanocrystalline Fe73.5Cu1Nb3 (SixB1-x)22.5 (x = 0.4-0.8) alloys. It is found that for all the alloys, except for x = 0.8, the soft magnetic properties of the ribbons quenched at the high melt temperature are better than those of the ribbon fabricated at the low melt temperature, in agreement with the previous observation, but the magnitude of improvement in the magnetic properties with increased melt temperature decreases with decreasing glass-forming ability. The present result emphasizes that the glass-forming ability of an alloy should be taken into account in considering the melt temperature effects.
Keywords: ULTRAFINE